Small size “DI-2” accelerator with the plasma current switch and inductive energy accum ulator as a material irradiation test rig - Yuferov, V.B.; Skibenko, E.I.; Buravilov, I.V.; Svichkar, А.S.; Ponamoriev, А.N.; Katrechko, V.V.; Nikulshina, V.V. (Вопросы атомной науки и техники, 2022)
This scientific paper delves into the basic characteristics of the updated “DI-2” accelerator, i.e., currents, voltages and pulse duration as a function of a delay time between the pulses generated by the major pulse current generator (PCG) and the PCG for plasma guns (PG). Consideration was given to the possibility of the use of heavy-current accelerators “VGIK-1” and “DI-2” as test rigs to study the effect of the heavy-current electron beam onto the surface of different materials to modify their physical and chemical properties. Наведено основні характеристики модернізованої установки “ДІ-2”, струм, напруга та тривалість імпульсу в залежності від часу затримки між імпульсами основного генератора імпульсного струму (ГІС) та ГІС плазмових гармат (ПГ). Розглянута можливість використання прискорювачів “ВГІК-1” та “ДІ-2” у якості дослідницького стенду по впливу сильнострумового електронного пучка на поверхню різних матеріалів для модифікації фізико-хімічних властивостей.